Phosphodiesterase 5 inhibitor acts as a potent agent sensitizing acute myeloid leukemia cells to 67‐kDa laminin receptor‐dependent apoptosis. Issue 18 (1st August 2013) - Kumazoe, Motofumi; Kim, Yoonhee; Bae, Jaehoon; Takai, Mika; Murata, Motoki; Suemasu, Yumi; Sugihara, Kaori; Yamashita, Shuya; Tsukamoto, Shuntaro; Huang, Yuhui; Nakahara, Kanami; Yamada, Koji; et al.
Abstract : (−)‐Epigallocatechin‐3‐ O ‐gallate (EGCG), a polyphenol in green tea, induces apoptosis in acute myeloid leukemia (AML) cells without affecting normal cells. In this study, we observed that cGMP acts as a cell death mediator of the EGCG‐induced anti‐AML effect through acid sphingomyelinase activation. EGCG activated the Akt/eNOS axis, a well‐known mechanism in vascular cGMP upregulation. We also observed that a major cGMP negative regulator, phosphodiesterase 5, was overexpressed in AML cells, and PDE5 inhibitor, an anti‐erectile dysfunction drug, synergistically enhanced the anti‐AML effect of EGCG. This combination regimen killed AML cells via overexpressed 67‐kDa laminin receptors. Abstract : ASM activation plays a pivotal role in the anti‐AML effect of EGCG. EGCG activated ASM via the eNOS/cGMP axis. PDE5, negative regulator of cGMP is overexpressed in AML cells. PDE5 inhibition significantly potentiated the anti‐AML effect of EGCG without affecting normal cells.